Fatigue analysis and fracture toughness of graphene reinforced carbon fibre polymer composites. Issue 2 (28th October 2020) - Tareq, Md Sarower; Jony, Bodiuzzaman; Zainuddin, Shaik; Al Ahsan, Mohammad; Hosur, Mahesh V.
Abstract: Three‐point flexural fatigue behaviour and mode I interlaminar fracture toughness of the carbon fibre reinforced polymer composites (CFRPCs) modified by the addition of graphene nanoplatelet (GnP) were investigated. CFRPCs without any addition of nanoparticles were also tested as control samples. Fatigue life was characterized by the two parameter Weibull distribution function and predicted using the combined Weibull and Sigmoidal model. It was found that incorporation of very small amount (0.1%) of GnP in the epoxy polymer matrix improved mean and predicted fatigue life up to 155% and 190% (0.5 failure probability), respectively. The critical mode I interlaminar fracture toughness of the GnP reinforced composites was found up to 40% higher than the control samples. The improvement achieved by incorporating GnP is discussed in terms of crack deflection mechanism by nanoparticles and scanning electron micrograph images of the fracture specimens that revealed strong interfacial bonding in the nanoreinforced specimens.